Revision of the Neotropical species of Pareucamptonyx Olmi (Hymenoptera, Dryinidae) with descriptions of new species - Martins, André L.; Domahovski, Alexandre C. (European Journal of Taxonomy, 2022)
The genus Pareucamptonyx Olmi, 1991 is endemic to the New World and comprises three described species, two from the Neotropical region and one from the Nearctic. Here is presented the first revision of species of Pareucamptonyx from the Neotropical region, including four new species described from Brazil: P. albopictus Martins sp. nov., P. kumagaiae Martins sp. nov., P. niger Martins sp. nov. and P. paranaensis Martins sp. nov. Detailed illustrations, distribution map, and key to females are provided, as well as a revised diagnosis of the genus and notes about the method of collection. Additionally, new distribution records for P. townesi (Olmi, 1984) are reported.